Հայաստանի ու Իրանի մոտեցումները տարածաշրջանային նոր մարտահրավերներին - Իսկանդարյան, Գոհար (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The last Artsakh war and the difficult situation around Armenia showed that after the collapse of the Soviet Union, the existing problems and challenges were not only not overcome, but new ones were added to them. The work presents Israel's military support to Azerbaijan during the 44-day war, which, according to the author, was carried out mainly due to Israel's insatiable desire to get closer to Iran's borders. From the available facts, the author comes to the conclusion that Israel has succeeded in this, which resulted in the severe tension between Azerbaijan and Iran during the recent period. Throughout the 44-day war, Iran tried to maintain the balance, but at the same time, its main task was to maintain its positions in the South Caucasus. The activation of Iranian diplomacy after the war is also noteworthy. Tehran tried to participate in the newly emerging situation with various proposals. After the war, it was obvious that Turkey's influence in the South Caucasus would increase even more, and also mercenaries and for the first time representatives of the Israeli intelligence service were brought to the region by Azerbaijan, which contradicts the security of the Iranian national, which he has spoken about several times. Even in Iran, having a good idea of the serious changes taking place in the region, they believe that they should also make the issues of changing the previous toolset and starting new quality discussions with the United States and the EU, concluding new temporary alliances a topic of discussion.
Keywords: Միջազգային հարաբերություններ; Հայաստան; Իրան